Effect of immunosuppressant drugs on Covid-19 patients to prevent cytokine storm in relation to periodontal tissue health: Pengaruh obat imunosupresan terhadap pasien Covid-19 untuk mencegah badai sitokin dalam hubungannya pada kesehatan jaringan periodontal - Patrisia Seroja Ningrum; Hasanuddin Thahir (Makassar Dental Journal, 2024)
Cytokines are small proteins released by many different cells in the body, including in the immune system that coordinate the bo-dy's response to fight infection and trigger inflammation. In Covid-19 patients, a cytokine storm attacks lung tissue and blood ves-sels. The condition causes the small air sacs in the lungs to fill with fluid, making it difficult for patients to breathe. This literature review discusses the effect of immunosuppressant drugs on Covid-19 patients to prevent cytokine storms, in relation to periodon-tal tissue health. A total of 25 sources were collected from various electronic search engines, and four articles were analysed using article synthesis tables. Long-term use of immunosuppressants will manifest in the oral cavity. It is concluded that patients with Covid-19 to prevent cytokine storms can be treated with the use of immunosuppressants, but their long-term use has an effect on periodontal tissue health.